MicroRNAs in heart transplant recipients - D. A. Velikiy; O. E. Gichkun; O. P. Shevchenko (Вестник трансплантологии и искусственных органов, 2017)
This review summarizes the current literature dedicated to the analysis of prognostic role of microRNAs in rejection of the transplanted heart. MicroRNAs are a class of small non-coding RNAs that regulate gene expression and affect various cellular functions. Variations of their profiles are noted at various pathological processes and rejection of solid organs. Presumably, measuring the level of microRNAs in heart transplant may have diagnostic and prognostic value in the assessment of risk of rejection and possibility of minimizing immunosuppressive therapy. Currently, accumulated clinical data on the role of the given biomarkers in heart transplantation are not enough, and further research on the relation of microRNAs levels and different clinical and laboratory parameters in heart recipients is necessary.